СТАВЛЕННЯ ЦАРСЬКОЇ ПРОКУРАТУРИ ТА СУДУ ЩОДО ДІЯЛЬНОСТІ ЧЛЕНІВ УСДРП ЧЕРНІГІВЩИНИ В УМОВАХ ПЕРШОЇ РОСІЙСЬКОЇ РЕВОЛЮЦІЇ (Zaporizhzhia Historical Review, 2021)
Contemporary records having been of great use, the article attempts to highlight the procuratorial supervision and autocracy juridical bodies activities as to the punishment of the Ukrainian social-democratic working party members for their revolutionary activity after the First State Duma dissolution.